2021
DOI: 10.5114/fmpcr.2021.108207
|View full text |Cite
|
Sign up to set email alerts
|

Different consequences of the treatment of osteoarthritis in gastrointestinal comorbidity with exocrine pancreatic insufficiency

Abstract: Background. Patients with OA require attention of specialists due to the high integrative risk of acute conditions caused by the use of drugs that successfully treat chronic pain, but lead to gastrointestinal complications . Objectives. The aim of the study was to evaluate the effect of anti-inflammatory treatment of primary osteoarthritis on joint and digestive functions, as well as the trophological status of patients with osteoarthritis under conditions of comorbidity with a pathology of the gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…Є низка робіт, що доводять обтяжливий вплив аскаридозу на перебіг шигельозу, черевного тифу, скарлатини, дифтерії, кору, туберкульозу тощо, проте вплив аскаридозу на перебіг ХП досі залишається недостатньо вивченим. Враховуючи розповсюдженість аскаридозу та ХП, вважали актуальним вивчення цієї мікст-патології [5][6][7].…”
unclassified
“…Є низка робіт, що доводять обтяжливий вплив аскаридозу на перебіг шигельозу, черевного тифу, скарлатини, дифтерії, кору, туберкульозу тощо, проте вплив аскаридозу на перебіг ХП досі залишається недостатньо вивченим. Враховуючи розповсюдженість аскаридозу та ХП, вважали актуальним вивчення цієї мікст-патології [5][6][7].…”
unclassified
“…Щорічно реєструється близько 65 тис. нових хворих [3][4][5]. Незважаючи на численні дослідження, що проводились із проблем паразитарних хвороб, залишається ще недостатньо розкритим патогенез органних і системних порушень, що визначають реабілітацію даного контингенту хворих.…”
unclassified
“…The presence of several comorbidities can be explained by aging, a significant risk factor for OA and other chronic diseases. The association of OA with gastrointestinal disease is usually attributed to the long-term use of analgesics, especially NSAIDs[19][20][21]. Studies have found uneven reporting of symptomatic gastrointestinal disorders, which warrants further study in patients with OA.…”
mentioning
confidence: 99%